Exploring the Impact of Nonlinear Dynamical Neurofeedback on Post-Cancer Cognitive Impairment and Cancer-Related Fatigue: Results of Interviews with Breast Cancer Survivors - Marian Luctkar-Flude; Jane Tyerman (Mary Ann Liebert, 2022)
Background: Breast cancer survivors may experience persistent cognitive impairment and fatigue after completion of cancer treatment, which negatively impacts their quality of life. Neurofeedback is a novel, non-invasive form of brain training reported to help with symptoms such as pain, fatigue, depression, anxiety, sleep problems, and cognitive decline; however, there is a lack of research exploring its use with cancer survivors. Objective: The objective of this study was to describe experiences of neurofeedback and its impact on the lives of post-treatment breast cancer survivors. Methods: This article describes the qualitative phase of a prospective pilot feasibility trial of a nonlinear dynamical neurofeedback intervention. Study participants had the option to participate in a semi-structured interview at follow-up. A sample of 12 breast cancer survivor clients participated in interviews 5?10 weeks after the completion of 20 sessions of nonlinear dynamic neurofeedback. This qualitative descriptive study employed thematic analysis of interview transcripts. Results: Qualitative analysis revealed two overarching themes of impact and experience and six subthemes: symptom impact, dramatic effect, symptom improvement, enjoyable experience, lack of side effects, and recommend for cancer survivors. Conclusion: Results of this qualitative descriptive study suggest that nonlinear dynamical neurofeedback had a dramatic and meaningful positive effect on persistent symptoms experienced by breast cancer survivors, without any negative side effects. Participants in our sample found the neurofeedback sessions to be enjoyable and recommend that they be offered to all cancer patients. Clinical trials with larger sample sizes are needed to corroborate our findings. Establishing clinical effectiveness could encourage adoption of neurofeedback into routine cancer care and health insurance coverage.